Mobility Extraction Methods in AlGaN/GaN HEMTs - Panzo, Eduardo Canga [UNESP] (2023)
This work deals with the comparison of the results of different methods for the extraction of charge mobility on AlGaN/GaN HEMT devices. They are, field effect mobility (μFE), effective mobility (μeff) and low field mobility (μ0), varying the gate length (Lg) and channel width (W), temperature (T) and gate voltage (Vg). In addition, the available data allowed the examination of figures of merit for the drain current (Id), output conductance (gd) and transconductance (gm), as well as the analysis of the behavior of the series resistance (RSD), threshold voltage (VT), and subthreshold slope (S). In this study, it was found that HEMTs have higher mobility for higher W, W/Lg and Vg, and for lower T in a range between 298K to 373K.